PENGARUH PENGGUNAAN METODE TOTALLY PHYSICAL RESPONCE (TPR) TERHADAP KETERAMPILAN BERBICARA MATA PELAJARAN BAHASA ARAB MI MIFTAHUR RAHMAN BENOWO SURABAYA - Afifah, Afifah; Mashuri, Imam (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to determine the effect of the total physical response method on students' speaking skills in Arabic class II MI Miftahur Rahman Benowo Surabaya. This type of research is an associative research with a population as well as a sample of all students of class II MI Miftahur Rahman Benowo Surabaya, totaling 60 students with details, namely class II A totaling 30 students and class B totaling 30 students. Data collection techniques in this study used a questionnaire totaling 15 items and scores based on the Likert scale to be given to 60 respondents who were carried out in google foam at the end of the lesson. This research uses a “google form” type of questionnaire and also an oral test. Data analysis in this study used the Pearson correlation test and simple linear regression test. This study uses Windows SPSS version 16.0. Based on the results of the Totally Physical Response method questionnaire in Arabic subjects, the percentage value of 55.43% is in the 50.01% - 75.00% interval. It can be interpreted that the use of the Totally Physical Response method in Arabic subjects is classified as good. Then the results of the oral test of speaking skills in Arabic subjects obtained an average value of 84.63% and a percentage value of 92% when consulted on the table of completeness criteria for learning outcomes, namely 86% - 100%. Thus, it can be interpreted that speaking skills in Arabic subjects are classified as very high. Therefore, it can be concluded that the method variable totally physical response (X) has an effect on the speaking skill variable (Y).